Markham's, Corporation Buildings. Johannesburg - Unknown (My University, 2011)
c/o Commissioner & Rissik Streets. Date Unknown.
Black and White Photograph.
Keywords: Markham's, Corporation Buildings, Commissioner street, Rissik street, Johannesburg.